Problems and Constructive Methods of Applied Control Theory for the Technical Systems with Distributed Parameters - Rapoport, Edgar; Pleshivtseva, Yuliya (2019 XXI International Conference Complex Systems: Control and Modeling Problems (CSCMP), 2019)
The approaches and methods for further development of applied theory of systems with distributed parameters are suggested to solve problems of open-loop controllability, construction of program optimization, a wide range of vector problems of optimal control and analytical designing of automatic regulators.